A Bohmian trajectory analysis of singular wave functions - Sanz, Ángel S.; Sanchez-Soto, Luis L.; Aiello, Andrea (Physics Letters A, 2024)
The Schrödinger equation admits smooth and finite solutions that spontaneously evolve into a singularity, even for a free particle. This blowup is generally ascribed to the intrinsic dispersive character of the associated time evolution. We resort to the notion of quantum Bohmian trajectories to relate this singular behavior to local phase variations, which generate an underlying velocity field responsible for driving the quantum flux toward the singular region.<br
Keywords: Bohmian mechanics; Singularities; Quantum flow; Self-focusing